Magnetic and Spectral Investigations of Some Mixed Ligand Complexes of Bis (Thioacetohydroxamato) Cobalt (II) - Verma, Savita; Kachhwaha, P.S.; Purohit, B.K.; P. Mathur, S. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of bis (thioacetohydroxamato) cobalt(II) with 1,10-phenanthroline and 2,2´-bipyridyl have been synthesized and their magnetic and spectral characteristics are reported.